A Study Into The Design Of A Soft-Computing Based Unsupervised Translator That Deals With Ambiguities (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
A key area of work, and indeed of challenges, in Machine Translation (MT) is dealing withambiguity. While in MT we aim to reduce the gap between human perception and machinesolution, we have repeatedly failed to show perfect results regarding this, and we continue tofailing getting human like translations from our machines. This conceptual paper reviews a fewof the commonly faced problems in ambiguity resolution when translating from English toBengali and vice versa, and, on the basis of this, aims to propose a soft-computing based methodin designing an English to Bengali and vice versa translator which may yield better results in thefuture. The implementation and hence the corresponding analytical studies thereafter are left asfuture work.